Locust Infestations and Mobile Phones: Exploring the Potential of Digital Tools to Enhance Early Warning Systems and Response Mechanisms - Halubanza, Brian; Phiri, Jackson; Nyirenda, Mayumbo; Nkunika , Phillip; Kunda, Douglas; Mulenga, James (Zambia ICT Journal, 2023)
This study aimed to investigate the knowledge levels and prevalence of locusts in the Sikaunzwe Agricultural camp in Zambia, as well as the association between mobile phone ownership and access to locust information. The study found that the majority of the sampled population were male, married, and engaged in farming as their primary occupation, with limited formal education. A significant proportion of the population had experienced locust outbreaks in the year preceding the survey, with the majority able to recognize the signs of locust outbreaks but only a small proportion having received training in locust management. Mobile phones were found to be a valuable tool for accessing and reporting locust information, but a significant proportion of the population did not own mobile phones. These findings have important policy implications for improving agricultural practices and management in the region, increasing training and awareness programs for locust management, and promoting the use of mobile technology to disseminate critical information to farmers in remote areas.